Refraction and wave matching in hyperbolic thermoelasticity - Józef Rafa (Biuletyn Wojskowej Akademii Technicznej, 2015)
The subject of the publication concerns the propagation of thermoelastic waves with a particular emphasis on the refraction of waves at the boundary of a layer laying (resting) on a halfspace. Analogously to the effect of wave matching, which appears in the case of acoustic and electromagnetic waves, the impedance of a thermoelastic wave has been introduced and its influence and the reflection andrefraction on the boundary at media has been investigated. The model of the medium describes a mutual coupling of mechanical and thermalinteractions with a wave type propagation of heat in media taken into account.[b]Keywords[/b]: hyperbolic thermoelasticity, wave impedance of a thermoelastic medium,refraction and wave matching